Cloning, overexpression, crystallization and preliminary X-ray crystallographic analysis of a slow-processing mutant of penicillin G acylase from Kluyvera citrophila - Varshney, Nishant Kumar; Ramasamy, Sureshkumar; Brannigan, James A.; Wilkinson, Anthony J.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2013)
{Kluyvera citrophila penicillin G acylase (KcPGA) has recently attracted increased attention relative to the well studied and commonly used Escherichia coli PGA (EcPGA) because KcPGA is more resilient to harsh conditions and is easier to immobilize for the industrial hydrolysis of natural penicillins to generate the 6-aminopenicillin (6-APA) nucleus, which is the starting material for semi-synthetic antibiotic production. Like other penicillin acylases, KcPGA is synthesized as a single-chain inactive pro-PGA, which upon autocatalytic processing becomes an active heterodimer of alpha and beta chains. Here, the cloning of the pac gene encoding KcPGA and the preparation of a slow-processing mutant precursor are reported. The purification, crystallization and preliminary X-ray analysis of crystals of this precursor protein are described. The protein crystallized in two different space groups, P1, with unit-cell parameters a = 54.0

Structural modelling of substrate binding and inhibition in penicillin V acylase from pectobacterium atrosepticum - Avinash, Vellore Sunder; Panigrahi, Priyabrata; Suresh, C. G.; Pundle, Archana V.; Ramasamy, Sureshkumar (Biochemical and Biophysical Research Communications, 2013)
Penicillin V acylases (PVAs) and bile salt hydrolases (BSHs) have considerable sequence and structural similarity; however, they vary significantly in their substrate specificity. We have identified a PVA from a Gram-negative organism, Pectobacterium atrosepticum (PaPVA) that turned out to be a remote homolog of the PVAs and BSHs reported earlier. Even though the active site residues were conserved in PaPVA it showed high specificity towards penV and interestingly the penV acylase activity was inhibited by bile salts. Comparative modelling and docking studies were carried out to understand the structural differences of the binding site that confer this characteristic property. We show that PaPVA exhibits significant differences in structure, which are in contrast to those of known PVAs and such enzymes from Gram-negative bacteria require further investigation. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Bile salt hydrolase; docking; Homology modelling; Inhibition; Pectobacterium; Penicillin acylase

Allostery mapping in enterococcus faecalis Bile Salt Hydrolase (BSH) - Yadav, Yashpal; Ramasamy, Sureshkumar (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Allostery; Bile salt hydrolase; MD Simulation

Chickpea Kunitz Inhibitor: a mechanistic basis for trypsin inhibition - Bendre, Ameya Dipak; Ramasamy, Sureshkumar; Suresh, C. G. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Chickpea; Kunitz Inhibitor; Protease

Crystal structure of AtGet3 Delta L, a chloroplast Get3 from Arabidopsis thaliana - Manu, M. S.; Ramasamy, Sureshkumar (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Arabidopsis thaliana; Get3; protein targeting

Engineering of the tat pathway and chaperons - Ghosh, Deepanjan; Ramasamy, Sureshkumar (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Protein transport; Signal sequence; Tat Pathway

Improved method for specificity annotation shows a distinct evolutionary divergence among the microbial enzymes of the cholylglycine hydrolase family - Panigrahi, Priyabrata; Sule, Manas; Sharma, Ranu; Ramasamy, Sureshkumar; Suresh, C. G. (Microbiology-SGM, 2014)
Bile salt hydrolases (BSHs) are gut microbial enzymes that play a significant role in the bile acid modification pathway. Penicillin V acylases (PVAs) are enzymes produced by environmental microbes, having a possible role in pathogenesis or scavenging of phenolic compounds in their microbial habitats. The correct annotation of such physiologically and industrially important enzymes is thus vital. The current methods relying solely on sequence homology do not always provide accurate annotations for these two members of the cholylglycine hydrolase (CGH) family as BSH/PVA enzymes. Here, we present an improved method [binding site similarity (BSS)-based scoring system] for the correct annotation of the CGH family members as BSH/PVA enzymes, which along with the phylogenetic information incorporates the substrate specificity as well as the binding site information. The BSS scoring system was developed through the analysis of the binding sites and binding modes of the available BSH/PVA structures with substrates glycocholic acid and penicillin V. The 198 sequences in the dataset were then annotated accurately using BSS scores as BSH/PVA enzymes. The dataset presented contained sequences from Gram-positive bacteria, Gram-negative bacteria and archaea. The clustering obtained for the dataset using the method described above showed a clear distinction in annotation of Gram-positive bacteria and Gram-negative bacteria Based on this clustering and a detailed analysis of the sequences of the CGH family in the dataset, we could infer that the CGH genes might have evolved in accordance with the hypothesis stating the evolution of diderms and archaea from the monoderms.

Structure of highly active BSH enzyme with subordinated post-translational excision - Chand, Deepak; Panigrahi, Priyabrata; Ramasamy, Sureshkumar; Suresh, C. G. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Bile salt hydrolase; Mutagenesis; X-ray crystallography

Biochemical, structural and functional diversity between two digestive alpha-amylases from helicoverpa armigera - Bhide, Amey J.; Channale, Sonal M.; Patil, Sucheta S.; Gupta, Vidya S.; Ramasamy, Sureshkumar; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2015)
Background: Helicoverpa armigera (Lepidoptera) feeds on various plants using diverse digestive enzymes as one of the survival tool-kit. The aim of the present study was to understand biochemical properties of recombinant alpha-amylases of H. armigera viz., HaAmy1 and HaAmy2. Methods: The open reading frames of HaAmy1 and HaAmy2 were cloned in Pichia pastoris and expressed heterologously. Purified recombinant enzymes were characterized for their biochemical and biophysical attributes using established methods. Results: Sequence alignment and homology modeling showed that HaAmy1 and HaAmy2 were conserved in their amino acid sequences and structures. HaAmy1 and HaAmy2 showed optimum activity at 60 degrees C; however, they differed in their optimum pH. Furthermore, HaAmy2 showed higher affinity for starch and amylopectin whereas HaAmy1 had higher catalytic efficiency. HaAmy1 and HaAmy2 were inhibited to the same magnitude by a synthetic amylase inhibitor (acarbose) while wheat amylase inhibitor showed about 2-fold higher inhibition of HaAmy1 than HaAmy2 at pH 7 while 6-fold difference at pH 11. Interactions of HaAmy1 and HaAmy2 with wheat amylase inhibitor revealed 2:1 stoichiometric ratio and much more complex interaction with HaAmy1. Conclusions: The diversity of amylases in perspective of their biochemical and biophysical properties, and their differential interactions with amylase inhibitors signify the potential role of these enzymes in adaptation of H. armigera on diverse plant diets. General significance: Characterization of digestive enzymes of H. armigera provides the molecular basis for the polyphagous nature and thus could assist in designing future strategies for the insect control. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: alpha-amylases; Amylase inhibitors; Digestive enzymes; Enzyme activity; Helicoverpa armigera

Engineering proteins for thermostability with iRDP web server - Panigrahi, Priyabrata; Sule, Manas; Ghanate, Avinash; Ramasamy, Sureshkumar; Suresh, C. G. (Plos One, 2015)
Engineering protein molecules with desired structure and biological functions has been an elusive goal. Development of industrially viable proteins with improved properties such as stability, catalytic activity and altered specificity by modifying the structure of an existing protein has widely been targeted through rational protein engineering. Although a range of factors contributing to thermal stability have been identified and widely researched, the in silico implementation of these as strategies directed towards enhancement of protein stability has not yet been explored extensively. A wide range of structural analysis tools is currently available for in silico protein engineering. However these tools concentrate on only a limited number of factors or individual protein structures, resulting in cumbersome and time-consuming analysis. The iRDP web server presented here provides a unified platform comprising of iCAPS, iStability and iMutants modules. Each module addresses different facets of effective rational engineering of proteins aiming towards enhanced stability. While iCAPS aids in selection of target protein based on factors contributing to structural stability, iStability uniquely offers in silico implementation of known thermostabilization strategies in proteins for identification and stability prediction of potential stabilizing mutation sites. iMutants aims to assess mutants based on changes in local interaction network and degree of residue conservation at the mutation sites. Each module was validated using an extensively diverse dataset. The server is freely accessible at http://irdp.ncl.res.in and has no login requirements.

Penicillin V acylase from pectobacterium atrosepticum exhibits high specific activity and unique kinetics - Avinash, Vellore Sunder; Ramasamy, Sureshkumar; Suresh, C. G.; Pundle, Archana (International Journal of Biological Macromolecules, 2015)
Penicillin V acylases (PVAs, E.C.3.5.11) belong to the Ntn hydrolase super family of enzymes that catalyze the deacylation of the side chain from phenoxymethyl penicillin (penicillin V). Penicillin acylases find use in the pharmaceutical industry for the production of semi-synthetic antibiotics. PVAs employ the N-terminal cysteine residue as catalytic nucleophile and are structurally and evolutionarily related to bile salt hydrolases (BSHs). Here, we report the cloning and characterization of a PVA enzyme from the Gram-negative plant pathogen, Pectobacterium atrosepticum (PaPVA). The enzyme was cloned and expressed in Escherichia coli attaining a very high yield (250 mg/l) and a comparatively high specific activity (430 IU/mg). The enzyme showed marginally better pH and thermo-stability over PVAs characterized from Gram-positive bacteria. The enzyme also showed enhanced activity in presence of organic solvents and detergents. The enzyme kinetics turned out to be significantly different from that of previously reported PVAs, displaying positive cooperativity and substrate inhibition. The presence of bile salts had a modulating effect on PaPVA activity. Sequence analysis and characterization reveal the distinctive nature of these enzymes and underscore the need to study PVAs from Gram-negative bacteria. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cooperative; Enzyme kinetics; Gram-negative; Penicillin V acylase; Substrate inhibition

Sequence and structure-based comparative analysis to assess, identify and improve the thermostability of penicillin G acylases - Panigrahi, Priyabrata; Chand, Deepak; Mukherji, Ruchira; Ramasamy, Sureshkumar; Suresh, C. G. (Journal of Industrial Microbiology & Biotechnology, 2015)
Penicillin acylases are enzymes employed by the pharmaceutical industry for the manufacture of semi-synthetic penicillins. There is a continuous demand for thermostable and alkalophilic enzymes in such applications. We have carried out a computational analysis of known penicillin G acylases (PGAs) in terms of their thermostable nature using various protein-stabilizing factors. While the presence of disulfide bridges was considered initially to screen putative thermostable PGAs from the database, various other factors such as high arginine to lysine ratio, less content of thermolabile amino acids, presence of proline in beta-turns, more number of ion-pair and other non-bonded interactions were also considered for comparison. A modified consensus approach designed could further identify stabilizing residue positions by site-specific comparison between mesostable and thermostable PGAs. A most likely thermostable enzyme identified from the analysis was PGA from Paracoccus denitrificans (PdPGA). This was cloned, expressed and tested for its thermostable nature using biochemical and biophysical experiments. The consensus site-specific sequence-based approach predicted PdPGA to be more thermostable than Escherichia coli PGA, but not as thermostable as the PGA from Achromobacter xylosoxidans. Experimental data showed that PdPGA was comparatively less thermostable than Achromobacter xylosoxidans PGA, although thermostability factors favored a much higher stability. Despite being mesostable, PdPGA being active and stable at alkaline pH is an advantage. Finally, several residue positions could be identified in PdPGA, which upon mutation selectively could improve the thermostability of the enzyme.
Keywords: Alkalistable; beta-lactam antibiotics; Consensus approach; Disulfide bridge; Ion pairs; Penicillin acylase; Thermostability

Structure mediation in substrate binding and post-translational processing of penicillin acylases: Information from mutant structures of Kluyvera citrophila penicillin G acylase - Chand, Deepak; Varshney, NishantKumar; Ramasamy, Sureshkumar; Panigrahi, Priyabrata; Brannigan, James A.; Wilkinson, Anthony J.; Suresh, C. G. (Protein Science, 2015)
Penicillin acylases are industrially important enzymes for the production of 6-APA, which is used extensively in the synthesis of secondary antibiotics. The enzyme translates into an inactive single chain precursor that subsequently gets processed by the removal of a spacer peptide connecting the chains of the mature active heterodimer. We have cloned the penicillin G acylase from Kluyvera citrophila (KcPGA) and prepared two mutants by site-directed mutagenesis. Replacement of N-terminal serine of the beta-subunit with cysteine (Ser beta 1Cys) resulted in a fully processed but inactive enzyme. The second mutant in which this serine is replaced by glycine (Ser beta 1Gly) remained in the unprocessed and inactive form. The crystals of both mutants belonged to space group P1 with four molecules in the asymmetric unit. The three-dimensional structures of these mutants were refined at resolutions 2.8 and 2.5 angstrom, respectively. Comparison of these structures with similar structures of Escherichia coli PGA (EcPGA) revealed various conformational changes that lead to autocatalytic processing and consequent removal of the spacer peptide. The large displacements of residues such as Arg168 and Arg477 toward the N-terminal cleavage site of the spacer peptide or the conformational changes of Arg145 and Phe146 near the active site in these structures suggested probable steps in the processing dynamics. A comparison between the structures of the processed Serb1Cys mutant and that of the processed form of EcPGA showed conformational differences in residues Arg alpha 145, Phe alpha 146, and Phe beta 24 at the substrate binding pocket. Three conformational transitions of Arg alpha 145 and Phe alpha 146 residues were seen when processed and unprocessed forms of KcPGA were compared with the substrate bound structure of EcPGA. Structure mediation in activity difference between KcPGA and EcPGA toward acyl homoserine lactone (AHL) is elucidated.
Keywords: acyl homoserine lactone; autocatalytic processing; conformational changes; KcPGA_Ser beta 1Cys; KcPGA_Ser beta 1Gly; Ntn hydrolase

Characterization of two coleopteran alpha-amylases and molecular insights into their differential inhibition by synthetic alpha-amylase inhibitor, acarbose - Channale, Sonal M.; Bhide, Amey J.; Yadav, Yashpal; Kashyap, Garima; Pawar, Pankaj K.; Maheshwari, V. L.; Ramasamy, Sureshkumar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2016)
Post-harvest insect infestation of stored grains makes them unfit for human consumption and leads to severe economic loss. Here, we report functional and structural characterization of two coleopteran alpha-amylases viz. Callosobruchus chinensis alpha-amylase (CcAmy) and Tribolium castaneum alpha-amylase (TcAmy) along with their interactions with proteinaceous and non-proteinaceous alpha-amylase inhibitors. Secondary structural alignment of CcAmy and TcAmy with other coleopteran alpha-amylases revealed conserved motifs, active sites, di-sulfide bonds and two point mutations at spatially conserved substrate or inhibitor binding sites. Homology modeling and molecular docking showed structural differences between these two enzymes. Both the enzymes had similar optimum pH values but differed in their optimum temperature. Overall, pattern of enzyme stabilities were similar under various temperature and pH conditions. Further, CcAmy and TcAmy differed in their substrate affinity and catalytic efficiency towards starch and amylopectin. HPLC analysis detected common amylolytic products like maltose and maltotriose while glucose and malto-tetrose were unique in CcAmy and TcAmy catalyzed reactions respectively. At very low concentrations, wheat alpha-amylase inhibitor was found to be superior over the acarbose as far as complete inhibition of amylolytic activities of CcAmy and TcAmy was concerned. Mechanism underlying differential amylolytic reaction inhibition by acarbose was discussed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Acarbose; alpha-amylase; alpha-amylase inhibitor; Callosobruchus chinensis; Coleoptera; Tribolium castaneum

Highly active bile salt hydrolase from enterococcus faecalis shows positive cooperative kinetics - Chand, Deepak; Ramasamy, Sureshkumar; Suresh, C. G. (Process Biochemistry, 2016)
Bile salt hydrolase (BSH; cholylglycine hydrolase, EC 3.5.1.24) is an important enzyme that catalyses the deconjugation of bile acids conjugated with glycine or taurine and assists in the reduction of blood cholesterol levels. In the present study, we report the cloning, overexpression and characterisation of BSH gene from a gut-associated microbe Enterococcus faecalis (EfBSH). The overexpressed protein in Escherichia coli was purified to homogeneity. Optimum pH and temperature for activity were found to be 5.0 and 50 degrees C, respectively. The enzyme was considerably stable in the pH range of 5.0-7.0 and at a temperature of up to 50 degrees C. It showed high specific activity of 1390 U mg(-1) and 1289 U mg-1 for substrates such as glycocholic acid (GCA) and glycodeoxycholic acid (GDCA), respectively. The effect of additives on enzyme activity was assessed, and the detergent Triton X showed a marginally enhanced activity. The enzyme demonstrated unique enzyme kinetics of non-linear regression, thereby displaying positive cooperativity. In addition, the modulating effect of the non-substrate ligand Pen V on the hydrolysing ability of EfBSH towards bile acid such as GDCA was measured. It was observed that Pen V significantly enhanced the BSH activity. This is markedly different from the previously reported competitive inhibition of BSH activity by Pen V. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Allosteric regulation; Bile acids; Bile salt hydrolase; Enzyme kinetics; Gut organism; Penicillin V acylase

Penicillin acylases revisited: importance beyond their industrial utility - Avinash, Vellore Sunder; Pundle, Archana Vishnu; Ramasamy, Sureshkumar; Suresh, Cheravakkattu Gopalan (Critical Reviews In Biotechnology, 2016)
It is of great importance to study the physiological roles of enzymes in nature; however, in some cases, it is not easily apparent. Penicillin acylases are pharmaceutically important enzymes that cleave the acyl side chains of penicillins, thus paving the way for production of newer semi-synthetic antibiotics. They are classified according to the type of penicillin (G or V) that they preferentially hydrolyze. Penicillin acylases are also used in the resolution of racemic mixtures and peptide synthesis. However, it is rather unfortunate that the focus on the use of penicillin acylases for industrial applications has stolen the spotlight from the study of the importance of these enzymes in natural metabolism. The penicillin acylases, so far characterized from different organisms, show differences in their structural nature and substrate spectrum. These enzymes are also closely related to the bacterial signalling phenomenon, quorum sensing, as detailed in this review. This review details studies on biochemical and structural characteristics of recently discovered penicillin acylases. We also attempt to organize the available insights into the possible in vivo role of penicillin acylases and related enzymes and emphasize the need to refocus research efforts in this direction.
Keywords: beta-lactam; choloyl glycine; in vivo role; Ntn hydrolases; pathogenicity; quorum sensing; regulation; signalling

Structural analysis of a penicillin V acylase from pectobacterium atrosepticum confirms the importance of two Trp residues for activity and specificity - Avinash, Vellore Sunder; Panigrahi, Priyabrata; Chand, Deepak; Pundle, Archana; Suresh, Cheravakattu Gopalan; Ramasamy, Sureshkumar (Journal of Structural Biology, 2016)
Penicillin V acylases (PVA) catalyze the deacylation of the beta-lactam antibiotic phenoxymethylpenicillin (Pen V). They are members of the Ntn hydrolase family and possess an N-terminal cysteine as the main catalytic nucleophile residue. They form the evolutionarily related cholylglycine hydrolase (CGH) group which includes bile salt hydrolases (BSH) responsible for bile deconjugation. Even though a few PVA and BSH structures have been reported, no structure of a functional PVA from Gram-negative bacteria is available. Here, we report the crystal structure of a highly active PVA from Gram-negative Pectobacterium atrosepticum (PaPVA) at 2.5 angstrom resolution. Structural comparison with PVAs from Gram-positive bacteria revealed that PaPVA had a distinctive tetrameric structure and active site organization. In addition, mutagenesis of key active site residues and biochemical characterization of the resultant variants elucidated the role of these residues in substrate binding and catalysis. The importance of residue Trp23 and Trp87 side chains in binding and correct positioning of Pen V by PVAs was confirmed using mutagenesis and substrate docking with a 15 ns molecular dynamics simulation. These results establish the unique nature of Gram-negative CGHs and necessitate further research about their substrate spectrum. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Aromatic stacking; Cholylglycine hydrolase; molecular dynamics; Mutagenesis; Oligomeric interactions

Structural-functional insights and studies on saccharide binding of Sophora japonica seed lectin - Yadav, Priya; Shahane, Ganesh; Ramasamy, Sureshkumar; Sengupta, Durba; Gaikwad, Sushama (International Journal of Biological Macromolecules, 2016)
Functional and conformational transitions of the Sophora japonica seed lectin (SJL) were studied in detail using bioinformatics and biophysical tools. Homology model of the lectin displayed all the characteristics of the legume lectin monomer and the experimental observations correlated well with the structural information. In silico studies were performed by protein-ligand docking, calculating the respective binding energies and the residues involved in the interactions were derived from LigPlot(+) analysis. Fluorescence titrations showed three times higher affinity of T-antigen disaccharide than N-acetyl galactosamine (GaINAc) towards SJL indicating extended sugar binding site of the lectin. Thermodynamic parameters of T-antigen binding to SJL indicated the process to be endothermic and entropically driven while those of GaINAc showed biphasic process. SDS-PAGE showed post-translationally modified homotetrameric species of the lectin under native conditions. In presence of guanidine hydrochloride (0.5-5.0 M), the tetramer first dissociated into dimers followed by unfolding of the protein as indicated by size exclusion chromatography, fluorescence and CD spectroscopy. Different structural rearrangements were observed during thermal denaturation of SJL at physiological pH 7.2, native pH 8.5 and molten globule inducing pH 1.0. Topological information revealed by solute quenching studies at respective pH indicated differential hydrophobic environment and charge density around tryptophan residues. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Dissociation; docking; Homology model; Ligand binding; Sophora japonica seed lectin; Thermal transitions

Genomic and functional characterization of coleopteran insect-specific alpha-amylase inhibitor gene from amaranthus species - Bhide, Amey J.; Channale, Sonal M.; Yadav, Yashpal; Bhattacharjee, Kabita; Pawar, Pankaj K.; Maheshwari, V. L.; Gupta, Vidya S.; Ramasamy, Sureshkumar; Giri, Ashok P. (Plant Molecular Biology, 2017)
The smallest 32 amino acid alpha-amylase inhibitor from Amaranthus hypochondriacus (AAI) is reported. The complete gene of pre-protein (AhAI) encoding a 26 amino acid (aa) signal peptide followed by the 43 aa region and the previously identified 32 aa peptide was cloned successfully. Three cysteine residues and one disulfide bond conserved within known alpha-amylase inhibitors were present in AhAI. Identical genomic and open reading frame was found to be present in close relatives of A. hypochondriacus namely Amaranthus paniculatus, Achyranthes aspera and Celosia argentea. Interestingly, the 3'UTR of AhAI varied in these species. The highest expression of AhAI was observed in A. hypochondriacus inflorescence; however, it was not detected in the seed. We hypothesized that the inhibitor expressed in leaves and inflorescence might be transported to the seeds. Sub-cellular localization studies clearly indicated the involvement of AhAI signal peptide in extracellular secretion. Full length rAhAI showed differential inhibition against alpha-amylases from human, insects, fungi and bacteria. Particularly, alpha-amylases from Helicoverpa armigera (Lepidoptera) were not inhibited by AhAI while Tribolium castaneum and Callosobruchus chinensis (Coleoptera) alpha-amylases were completely inhibited. Molecular docking of AhAI revealed tighter interactions with active site residues of T. castaneum alpha-amylase compared to C. chinensis alpha-amylase, which could be the rationale behind the disparity in their IC50. Normal growth, development and adult emergence of C. chinensis were hampered after feeding on rAhAI. Altogether, the ability of AhAI to affect the growth of C. chinensis demonstrated its potential as an efficient bio-control agent, especially against stored grain pests.

Medium constituents mediated engineering for size and shape tuning of gold nanocrystallites - Suresh, Anil K.; Vijay, Veena; Hameed, Bahrudeen S.; Ramasamy, Sureshkumar; Sakthivel, Natarajan (Journal of Industrial and Engineering Chemistry, 2017)
The current investigation introduces the utilization of cell culture mediums as a novel source for the one plot synthesis as well as stabilization of metal nanoparticles. By varying the medium constituents we could control the size and shape distributions of the gold nanoparticles. Nanospheres of diameter 24 +/- 6 nm and 19 +/- 5 nm were produced using DMEM and M199 mediums respectively, nanoneedles of 150 +/- 50 nm using RPMI medium and nanoflowers of 60 +/- 25 nm using IMDM medium, with an overall yield of 91 +/- 2%. A remarkable decrease in the reaction duration (<3 min) was noted, irrespective of the growth mediums used. Fourier transform infrared spectroscopy and zeta potential measurements revealed them to have a common protenacious encapping agent with different overall surface charges of -23 +/- 3, -21 +/- 1, -24 +/- 2, and -20 +/- 1 mV for Au@DMEM, Au@RPMI, Au@IMDM and Au@M199 respectively. X-ray diffraction confirmed the purity and crystallinity of the particles with Bragg peaks at (111), (200), (220) and (311) for gold nanocrystals. This approach could lead to the creative utilization of novel eco-friendly sources for the production and size/shape control of nanoparticles. Moreover, the adopted methodology is absolutely green, robust and facile, offering new insights for sustainable synthesis for various biomedical and engineering applications. (C) 2017 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.

Penicillin V acylases from gram-negative bacteria degrade N-acylhomoserine lactones and attenuate virulence in Pseudomonas aeruginosa - Sunder, Avinash Vellore; Utari, Putri Dwi; Ramasamy, Sureshkumar; van Merkerk, Ronald; Quax, Wim; Pundle, Archana (Applied Microbiology and Biotechnology, 2017)
Virulence pathways in gram-negative pathogenic bacteria are regulated by quorum sensing mechanisms, through the production and sensing of N-acylhomoserine lactone (AHL) signal molecules. Enzymatic degradation of AHLs leading to attenuation of virulence (quorum quenching) could pave the way for the development of new antibacterials. Penicillin V acylases (PVAs) belong to the Ntn hydrolase superfamily, together with AHL acylases. PVAs are exploited widely in the pharmaceutical industry, but their role in the natural physiology of their native microbes is not clearly understood. This report details the characterization of AHL degradation activity by homotetrameric PVAs from two gram-negative plant pathogenic bacteria, Pectobacterium atrosepticum (PaPVA) and Agrobacterium tumefaciens (AtPVA). Both the PVAs exhibited substrate specificity for degrading long-chain AHLs. Exogenous addition of these enzymes into Pseudomonas aeruginosa greatly diminished the production of elastase and pyocyanin and biofilm formation and increased the survival rate in an insect model of acute infection. Subtle structural differences in the PVA active site that regulate specificity for acyl chain length have been characterized, which could reflect the evolution of AHL-degrading acylases in relation to the environment of the bacteria that produce them and also provide strategies for enzyme engineering. The potential for using these enzymes as therapeutic agents in clinical applications and a few ideas about their possible significance in microbial physiology have also been discussed.
Keywords: N-acylhomoserine lactone acylase; Ntn hydrolase; pathogenesis; Penicillin Vacylase; Quorum quenching

Analysis of Kunitz inhibitors from plants for comprehensive structural and functional insights - Bendre, Ameya D.; Ramasamy, Sureshkumar; Suresh, C. G. (International Journal of Biological Macromolecules, 2018)
Legume Kunitz type trypsin inhibitor (KTI) family is one of the most versatile families of proteins. A typical KTI features a single peptide folded in beta-trefoil manner, with the molecular weight about 20-22 kDa and two disulphide bonds. The members are known to inhibit a wide range of serpins proteases at the same time many of them possess unique features. Copaifera langsdoiffii Trypsin inhibitor (CTI) has a beta-trefoil fold made up of two non-covalently bound polypeptide chains with only a single disulfide bridge. Delonix regia Trypsin inhibitor (DrTI) has one amino acid insertion between P1 and P2 of the reactive site distorting its conformation. Bauhinia bauhinioides Cruzipain inhibitor (BbCI) has a conservative beta-trefoil fold but lacks disulfide bonds. Such subtle differences in structures make Kunitz inhibitors different from other inhibitor families. Most of the studies on these inhibitors are focused towards their proposed role in defense from insect pests and wounding but their exact physiological role in nature is still uncharted. Thus, it would be very interesting to closely analyze the structural details of these inhibitors in order to ascertain their biological role and other fascinating applications. (C) 2018 Elsevier B.V. All rights reserved.

Analysis of tail-anchored protein translocation pathway in plants - Manu, M. S.; Ghosh, Deepanjan; Chaudhari, Bhushan P.; Ramasamy, Sureshkumar (Biochemistry and Biophysics Reports, 2018)
Tail-anchored (TA) proteins are a special class of membrane proteins that carry out vital functions in all living cells. Targeting mechanisms of TA proteins are investigated as the best example for post-translational protein targeting in yeast. Of the several mechanisms, Guided Entry of Tail-anchored protein (GET) pathway plays a major role in TA protein targeting. Many in silico and in vivo analyses are geared to identify TA proteins and their targeting mechanisms in different systems including Arabidopsis thaliana. Yet, crop plants that grow in specific and/or different conditions are not investigated for the presence of TA proteins and GET pathway. This study majorly investigates GET pathway in two crop plants, Oryza sativa subsp. Indica and Solanum tuberosum, through detailed in silico analysis. 508 and 912 TA proteins are identified in Oryza sativa subsp. Indica and Solanum tuberosum respectively and their localization with respect to endoplasmic reticulum (ER), mitochondria, and chloroplast has been delineated. Similarly, the associated GET proteins are identified (Get1, Get3 and Get4) and their structural inferences are elucidated using homology modelling. Get3 models are based on yeast Get3. The cytoplasmic Get3 from O. sativa is identified to be very similar to yeast Get3 with conserved P-loop and TA binding groove. Three cytoplasmic Get3s are identified for S. tuberosum. Taken together, this is the first study to identify TA proteins and GET components in Oryza sativa subsp. Indica and Solanum tuberosum, forming the basis for any further experimental characterization of TA targeting and GET pathway mechanisms in crop plants.

Baicalein suppresses repeat tau fibrillization by sequestering oligomers - Sonawane, Shweta Kishor; Balmik, Abhishek Ankur; Boral, Debjyoti; Ramasamy, Sureshkumar; Chinnathambi, Subashchandrabose (Archives of Biochemistry and Biophysics, 2019)
Alzheimer's disease (AD) is a neurodegenerative disorder caused by protein misfolding, aggregation and accumulation in the brain. A large number of molecules are being screened against these pathogenic proteins but the focus for therapeutics is shifting towards the natural compounds as aggregation inhibitors, mainly due to their minimum adverse effects. Baicalein is a natural compound belonging to the class of flavonoids isolated from the Chinese herb Scutellaria baicalensis. Here we applied fluorescence, absorbance, microscopy, MALDI-TOF spectrophotometry and other biochemical techniques to investigate the interaction between Tau and Baicalein in vitro. We found the aggregation inhibitory properties of Baicalein for the repeat Tau. Overall, the potential of Baicalein in dissolving the preformed Tau oligomers as well as mature fibrils can be of utmost importance in therapeutics for Alzheimer's disease.
Keywords: Alzheimer disease; Baicalein; Microtubule assembly; Paired helical filaments; Protein aggregation; tau protein

Core-composite mediated separation of diverse nanoparticles to purity - Bhatt, Chandra S.; Nagaraj, Bharathkumar; Ghosh, Deepanjan; Ramasamy, Sureshkumar; Thapa, Ranjit; Marpu, Sreekar B.; Suresh, Anil K. (Soft Matter, 2019)
A generalized method for sorting nanoparticles based on their cores does not exist; it is an immediate necessity, and an approach incorporating cost-effectiveness and biocompatibility is in demand. Therefore, an efficient method for the separation of various mixed core-compositions or dissimilar metallic nanoparticles to their pure forms at the nano-bio interface was developed. Various simple core-combinations of monodispersed nanoparticles with dual cores, including silver plus gold, iron oxide plus gold and platinum plus gold, to the complex three-set core-combinations of platinum plus gold plus silver and platinum plus iron plus gold were sorted using step-gradient centrifugation in a sucrose suspension. Viscosity mediated differential terminal velocities of the nanoparticles permitted diversified dragging at different gradients allowing separation. Stability, purity and properties of the nanoparticles during separation were evaluated based on visual confirmation and by employing advanced instrumentations. Moreover, theoretical studies validated our experimental observations, revealing the roles of various parameters, such as the viscosity of sucrose, the density of the particles and the velocity and duration of centrifugation, involved during the separation process. This remarkably rapid, cost-efficient and sustainable strategy can be adapted to separate other cores of nanoparticles for various biomedical research purposes, primarily to understand nanoparticle induced toxicity and particle fate and transformations in natural biotic environments.

Structural insight into a membrane intrinsic Acyltransferase from Chlorobium tepidum - Boral, Debjyoti; Vankudoth, Koteswara Rao; Ramasamy, Sureshkumar (Current Microbiology, 2019)
The Lipid A component of the outer membrane of Gram-negative bacteria is an integral part of the permeability barrier known as LPS, which actively prevents the uptake of bactericidal compounds. It is clinically very significant, as it is known to elicit a strong immune response in the humans, through the TLR4 complex. The Lipid A species are synthesized through a highly conserved multistep biosynthetic pathway. The final step is catalyzed by acyltransferases of the HtrB/MsbB family, which are members of a superfamily of enzymes, present in all domains of life with important roles to play in various biological processes. The investigation of a putative dual functioning enzyme which can add both laurate and myristate residues to the (Kdo)(2)-lipid IVA (precursor of Lipid A) would give a snapshot into the versatility of substrates that these enzymes catalyze. In this study we have cloned and purified to homogeneity, such a putative dual functional acyltransferase from Chlorobium tepidum, and attempted to study the enzyme in more details in terms of its sequence and structural aspects, as it lacks conserved residues with other enzymes of the same family.

Structural insights into the unique inhibitory mechanism of Kunitz type trypsin inhibitor from Cicer arietinum L. Vol. 37 - Bendre, Ameya D.; Suresh, C. G.; Shanmugam, Dhanasekaran; Ramasamy, Sureshkumar (Journal of Biomolecular Structure & Dynamics, 2019)
Kunitz-type trypsin inhibitors bind to the active pocket of trypsin causing its inhibition. Plant Kunitz-type inhibitors are thought to be important in defense, especially against insect pests. From sequence analysis of various Kunitz-type inhibitors from plants, we identified CaTI2 from chickpea as a unique variant lacking the functionally important arginine residue corresponding to the soybean trypsin inhibitor (STI) and having a distinct and unique inhibitory loop organization. To further explore the implications of these sequence variations, we obtained the crystal structure of recombinant CaTI2 at 2.8 angstrom resolution. It is evident from the structure that the variations in the inhibitory loop facilitates non-substrate like binding of CaTI2 to trypsin, while the canonical inhibitor STI binds to trypsin in substrate like manner. Our results establish the unique mechanism of trypsin inhibition by CaTI2, which warrant further research into its substrate spectrum.
Keywords: Chickpea; crystal structure; inhibitory loop; Kunitz trypsin inhibitor; Trypsin

Zebrafish acid ceramidase: expression in Pichia pastoris GS115and biochemical characterization - Rajput, Vijay B.; Karthikeyan, Muthukumarasamy; Ramasamy, Sureshkumar (International Journal of Biological Macromolecules, 2019)
Acid ceramidase (N-acylsphingosine deacylase EC 3.5.1.23; AC) catalyzes the hydrolysis of ceramide into sphingosine (SPH) and free fatty acid. Zebrafish acid ceramidase (AC) has 60% homology with the human AC). Mutations in the human AC gene asah1 are known to cause Farber disease and spinal muscular atrophy with progressive myoclonic epilepsy. Zebrafish AC was overexpressed in Pichia pastoris by inserting asah1b gene into the genome. The majority of the overexpressed enzyme was secreted into the culture medium and purified to apparent homogeneity by stepwise chromatography. The recombinant protein was glycosylated precursor, that further undergoes limited autoproteolytic processing into two subunits (alpha and beta) which are visible in SDS-PAGE. The zebrafish AC is heterodimer associated with an inter-subunit disulfide bond. SDS-PAGE estimated the mass of native enzyme to be approximately 50 kDa & size exclusion chromatography estimated the mass of the active enzyme as approximately 100 kDa, suggesting the formation of a dimer of heterodimers. The protein was secreted as a mixture of processed and unprocessed forms in the culture media. A preliminary characterization of purified zebrafish AC was done by an enzyme assay. The zebrafish AC expressed in Pichia pastoris would be used for further structural and functional analysis. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Autoproteolytic processing; Pichia pastoris; Zebrafish acid ceramidase

Archeal Di-O-geranylgeranyl glyceryl phosphate synthase of a UbiA superfamily member provides insight into the multiple human diseases - Boral, Debjyoti; Rao, Vamkudoth Koteswara; Ramasamy, Sureshkumar (Protein and Peptide Letters, 2020)
One of the unique characteristic features of the domain archaea, are the lipids that form the hydrophobic core of their cell membrane. These membrane lipids are characterized by distinctive isoprenoid biochemistry and the building blocks are two core lipid structures, sn-2,3-diphytanyl glycerol diether (archaeol) and sn-2,3-dibiphytanyl diglycerol tetraether (caldarchaeol). Archaeol has two phytanyl chains (C-20 in a bilayer structure connected to the glycerol moiety by an ether bond. The enzyme involved in this bilayer formation is Di-O-Geranylgeranyl Glyceryl Phosphate Synthase (DGGGPS), which is a member of a very versatile superfamily of enzymes known as UbiA superfamily. Multiple sequence analysis of the typical members of the UbiA superfamily indicates that the majority of conserved residues are located around the central cavity of these enzymes. Interestingly few of these conserved residues in the human homologs are centrally implicated in several human diseases, on basis of the major mutations reported against these diseases in the earlier clinical studies. It remains to he investigated about the role of these conserved residues in the biochemistiy of these enzymes. The binding and active site of these enzymes found to be similar architecture but have different substrate affinities ranging from aromatic to linear compounds. So further investigation of UbiA superfamily may be translated to novel therapeutic and diagnostic application of these proteins in human disease management.
Keywords: Archeal lipids; biA superfamily; DGGGPS; genetic diseases; lipid synthesis; membrane protein

EGCG impedes human Tau aggregation and interacts with Tau - Sonawane, Shweta Kishor; Chidambaram, Hariharakrishnan; Boral, Debjyoti; Gorantla, Nalini Vijay; Balmik, Abhishek Ankur; Dangi, Abha; Ramasamy, Sureshkumar; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
Tau aggregation and accumulation is a key event in the pathogenesis of Alzheimer's disease. Inhibition of Tau aggregation is therefore a potential therapeutic strategy to ameliorate the disease. Phytochemicals are being highlighted as potential aggregation inhibitors. Epigallocatechin-3-gallate (EGCG) is an active phytochemical of green tea that has shown its potency against various diseases including aggregation inhibition of repeat Tau. The potency of EGCG in altering the PHF assembly of full-length human Tau has not been fully explored. By various biophysical and biochemical analyses like ThS fluorescence assay, MALDI-TOF analysis and Isothermal Titration Calorimetry, we demonstrate dual effect of EGCG on aggregation inhibition and disassembly of full-length Tau and their binding affinity. The IC50 for Tau aggregation by EGCG was found to be 64.2 mu M.

Functional stability and structural transitions of a kunitz trypsin inhibitor from chickpea (CaTI2) - Bendre, Ameya D.; Shukla, Ekta; Ramasamy, Sureshkumar (Protein Journal, 2020)
Enzymes are important tools for various applications. We have studied structural transitions and functional stability of a Kunitz trypsin inhibitor from Chickpea (CaTI2), a potent insect gut-protease inhibitor, under different stress conditions like non-neutral pH, elevated temperature and co-solvent concentrations. CaTI2 was cloned and expressed in an eukaryotic systemP. pastorisand was investigated for conformational transitions using circular dichroism spectroscopy, differential scanning fluorimetry and activity assay. Native CaTI2 has a sheet dominant structure with 40% beta sheets and possess a single tryptophan residue situated in the hydrophobic core of the enzyme. The recombinant inhibitor maintained its maximum activity under alkaline pH with its secondary structure intact between pH 6-10. CaTI2 was observed to be thermally stable up to 55 degrees C with aT(m) of 61.3 degrees C above which the protein unfolds. On treating with chemical denaturant (urea), the CaTI2 lost its inhibitory potential and native conformation beyond 2 M urea concentration. Moreover, the protein unfolded at lower temperatures as the concentration of denaturant increased, suggesting more complex structural changes. Further, the stability of the inhibitor was found to be directly proportional to the solvent polarity. The data, herein offers significant information of inhibitor stability and activity which could be exploited for its further development into an effective pesticide. [GRAPHICS] .
Keywords: Chickpea; Circular dichroism spectroscopy; Differential scanning fluorimetry; Functional stability; Kunitz trypsin inhibitor

Process development for 6-aminopenicillanic acid production using lentikats-encapsulated escherichia coli cells expressing penicillin V acylase - Sawant, Amol M.; Sunder, Avinash Vellore; Vamkudoth, Koteswara Rao; Ramasamy, Sureshkumar; Pundle, Archana (ACS Omega, 2020)
Penicillin V acylase (PVA, EC 3.5.1.11) hydrolyzes the side chain of phenoxymethylpenicillin (Pen V) and finds application in the manufacture of the pharmaceutical intermediate 6-aminopenicillanic acid (6-APA). Here, we report the scale-up of cultivation of Escherichia coli whole cells expressing a highly active PVA from Pectobacterium atrosepticum and their encapsulation in polyvinyl alcohol-poly(ethylene glycol) Lentikats hydrogels. A biocatalytic process for the hydrolysis of 2% (w/v) Pen V was set up in a 2 L reactor using the Lentikats-immobilized whole cells, with a customized setup to enable continuous downstream processing of the reaction products. The biocatalytic reaction afforded complete conversion of Pen V for 10 reaction cycles, with an overall 90% conversion up to 50 cycles. The bioprocess was further scaled up to the pilot-scale at 10 L, enabling complete conversion of Pen V to 6-APA for 10 cycles. The 6-APA and phenoxy acetic acid products were recovered from downstream processing with isolated yields of 85-90 and 87-92%, respectively. Immobilization in Lentikats beads improved the stability of the whole cells on storage, maintaining 90-100% activity and similar conversion efficiency after 3 months at 4 degrees C. The robust PVA biocatalyst can be employed in a continuous process to provide a sustainable route for bulk 6-APA production from Pen V.

Structural and enzymatic analysis of a dimeric cholylglycine hydrolase like acylase active on N-acyl homoserine lactones - Philem, Pushparani D.; Yadav, Yashpal; Sunder, Avinash Vellore; Ghosh, Deepanjan; Prabhune, Asmita; Ramasamy, Sureshkumar (Biochimie, 2020)
The prevalence of substrate cross-reactivity between AHL acylases and beta-lactam acylases provides a glimpse of probable links between quorum sensing and antibiotic resistance in bacteria. Both these enzyme classes belong to the N-terminal nucleophile (Ntn)-hydrolase superfamily. Penicillin V acylases alongside bile salt hydrolases constitute the cholylglycine hydrolase (CGH) group of the Ntn-hydrolase superfamily. Here we report the ability of two acylases, Slac1 and Slac2, from the marine bacterium Shewanella loihica PV4 to hydrolyze AHLs. Three-dimensional structure of Slac1 reveals the conservation of the Ntn hydrolase fold and CGH active site, making it a unique CGH exclusively active on AHLs. Slac1homologs phylogenetically cluster separate from reported CGHs and AHL acylases, thereby representing a functionally distinct sub-class of CGH that might have evolved as an adaptation to the marine environment. We hypothesize that Slac1 could provide the structural framework for understanding this subclass, and further our understanding of the evolutionary link between AHL acylases and beta-lactam acylases. (C) 2020 Elsevier B.V. and Societe Francaise de Biochimie et Biologie Moleculaire (SFBBM). All rights reserved.
Keywords: AHL acylase; Cholyolglycine hydrolase; Homodimer; Ntn-fold; Shewanella loihica-PV4

Structure and regulation of SWEET transporters in plants: an update - Anjali, Anjali; Fatima, Urooj; Manu, M. S.; Ramasamy, Sureshkumar; Senthil-Kumar, Muthappa (Plant Physiology and Biochemistry, 2020)
Sugar will eventually be exported transporters (SWEETs), a novel family of sugar transporters found in both eukaryotes and prokaryotes, facilitate sugar flux across the cell membrane. Although these transporters were first discovered in plants, their homologs have been reported in different organisms. SWEETs have critical roles in various developmental processes, including phloem loading, nectar secretion, and pathogen nutrition. The structure of bacterial homologs, called SemiSWEETs, has been well studied thus far. Here, we provide an overview of SWEET protein structure and dynamic function by analyzing the solved crystal structures and predicted models that are available for a few SWEETs in a monocot plant (rice) and dicot plant (Arabidopsis thaliana). Despite the advancement in structure-related studies, the regulation of SWEETs remains unknown. In light of reported regulatory mechanisms of a few other sugar transporters, we propose the regulation of SWEETs at the post-translational level. We then enumerate the potential post-translational modification sites in SWEETs using computational tools. Overall, in this review, we critically analyze SWEET protein structure in plants to predict the post-translational regulation of SWEETs. Such findings have a direct bearing on plant nutrition and defense and targeting the regulation at these levels will be important in crop improvement.
Keywords: oligomerization; Phosphorylation; Post-translational modification; Sugar transporters; Sugar will eventually be exported transporters

De novo structure prediction of meteorin and meteorin-like protein for identification of domains, functional receptor binding regions, and their high-risk missense variants - Shankar, S. Shiva; Banarjee, Reema; Jathar, Swaraj M.; Rajesh, S.; Ramasamy, Sureshkumar; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2024)
Meteorin (Metrn) and Meteorin-like (Metrnl) are homologous secreted proteins involved in neural development and metabolic regulation. In this study, we have performed de novo structure prediction and analysis of both Metrn and Metrnl using Alphafold2 (AF2) and RoseTTAfold (RF). Based on the domain and structural homology analysis of the predicted structures, we have identified that these proteins are composed of two functional domains, a CUB domain and an NTR domain, connected by a hinge/loop region. We have identified the receptor binding regions of Metrn and Metrnl using the machine-learning tools ScanNet and Masif. These were further validated by docking Metrnl with its reported KIT receptor, thus establishing the role of each domain in the receptor interaction. Also, we have studied the effect of non-synonymous SNPs on the structure and function of these proteins using an array of bioinformatics tools and selected 16 missense variants in Metrn and 10 in Metrnl that can affect the protein stability. This is the first study to comprehensively characterize the functional domains of Metrn and Metrnl at their structural level and identify the functional domains, and protein binding regions. This study also highlights the interaction mechanism of the KIT receptor and Metrnl. The predicted deleterious SNPs will allow further understanding of the role of these variants in modulating the plasma levels of these proteins in disease conditions such as diabetes.
Keywords: domains; Meteorin; meteorin-like; missense variants; protein-protein interactions; structure prediction